2021
DOI: 10.2478/popets-2021-0075
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Without Breaking: Identification and Mitigation of Non-Essential IoT Traffic

Abstract: Despite the prevalence of Internet of Things (IoT) devices, there is little information about the purpose and risks of the Internet traffic these devices generate, and consumers have limited options for controlling those risks. A key open question is whether one can mitigate these risks by automatically blocking some of the Internet connections from IoT devices, without rendering the devices inoperable. In this paper, we address this question by developing a rigorous methodology that relies on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 45 publications
(51 reference statements)
0
20
0
Order By: Relevance
“…A difference between our findings and the ones of the above works is that Amazon smart speakers in our study contact additional endpoints from Amazon, skills vendors, and third-parties that have never been reported before. For example, with respect to the endpoints reported in a 2021 study [72], we have observed 4 new Amazon domains (acsechocaptiveportal.com, amazon-dss.com, a2z.com, amazonalexa.com. ), 2 skills-specific endpoints (see skills row in Table 1) and 12 new third-party endpoints (see third party row in Table 1).…”
Section: Parallels With Other Iot Platformsmentioning
confidence: 93%
See 2 more Smart Citations
“…A difference between our findings and the ones of the above works is that Amazon smart speakers in our study contact additional endpoints from Amazon, skills vendors, and third-parties that have never been reported before. For example, with respect to the endpoints reported in a 2021 study [72], we have observed 4 new Amazon domains (acsechocaptiveportal.com, amazon-dss.com, a2z.com, amazonalexa.com. ), 2 skills-specific endpoints (see skills row in Table 1) and 12 new third-party endpoints (see third party row in Table 1).…”
Section: Parallels With Other Iot Platformsmentioning
confidence: 93%
“…Having such interface unlocked for developers and auditors would reveal the actual data being shared. Another example of a possible user defense is to selectively block network traffic that is not essential for the skill to work (e.g., using an approach similar to [72]). TABLE 14: Endpoint organizations observed in the network traffic from skills run on the Amazon Echo: only 32 skills exhibit non-Amazon endpoints.…”
Section: Possible Defensesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, recent work by Mandalari et al [19] describes a system that determines when privacy interventions break user desirable systems, but for internet-of-things devices instead of websites. Their system automatically distinguishes necessary traffic flows from noncore flows, and only applies privacy protections (i.e.…”
Section: Compatibility Of Privacy Protectionsmentioning
confidence: 99%
“…Peekaboo's hub is similar in spirit to cloudlets [67], but the key difference is that the computation running on the hub is structured and enforced using the operator-based manifest. Peekaboo is also inspired by past smart home hub/gateway/firewall projects [11], [14], [39], [51], [76]. Peekaboo has two major differences.…”
Section: Related Workmentioning
confidence: 99%